2018 IEEE Nuclear Science Symposium and Medical Imaging Conference Proceedings (NSS/MIC) 2018
DOI: 10.1109/nssmic.2018.8824767
|View full text |Cite
|
Sign up to set email alerts
|

Total variation and point spread function priors for MLEM reconstruction in Compton camera imaging

Abstract: The Compton camera is a gamma ray imaging device already employed in astronomy and still in investigation for clinical domain. A key point in the imaging process is the tomographic reconstruction step. When the acquisition parameters and the a priori information are correctly accounted for, iterative algorithms are able to produce accurate images by compensating for measurement uncertainties and statistical noise. In this work we focus on the list-mode maximum likelihood expectation maximization (LM-MLEM) algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the convergence speed of the adopted iterative reconstruction method was not sufficiently high because the imaging algorithms considered the high-energy γ-ray source located at a far distance, and the simulation programs developed at that time considered the simple detector system. Some studies have recently been conducted to improve the MLEM and compare it with other imaging models, with a focus on the application of Compton cameras in nuclear medicine and particle therapy [ 81 , 210 , 211 , 212 , 213 ]. Yabu et al [ 214 ] reported the superiority of the LM-MLEM method over SBP using a Si/CdTe Compton camera.…”
Section: Image Reconstruction Methods For Compton Imagingmentioning
confidence: 99%
“…However, the convergence speed of the adopted iterative reconstruction method was not sufficiently high because the imaging algorithms considered the high-energy γ-ray source located at a far distance, and the simulation programs developed at that time considered the simple detector system. Some studies have recently been conducted to improve the MLEM and compare it with other imaging models, with a focus on the application of Compton cameras in nuclear medicine and particle therapy [ 81 , 210 , 211 , 212 , 213 ]. Yabu et al [ 214 ] reported the superiority of the LM-MLEM method over SBP using a Si/CdTe Compton camera.…”
Section: Image Reconstruction Methods For Compton Imagingmentioning
confidence: 99%
“…), the concept of COR can be generalized to a volume of response (VOR), which represents the region in a 3D space where the origin of the event originates. Several approaches have been introduced to model the VORs into the reconstruction, see, for example [83,[88][89][90][91][92]. Among them, including a model of the point-spread-function (PSF) in image space as a convolution kernel is an extended option, see Fig.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Using specific edge-preserving priors and appropriate β values, image noise can be effectively reduced without loss of resolution. In spite of the great potential of Bayesian reconstruction, only few works report the use of priors for Compton-camera data [105,[108][109][110].…”
Section: Image Reconstructionmentioning
confidence: 99%